A systematic review of online education initiatives to develop students remote caring skills and practices. Issue 1 (31st December 2022) - Nowell, Lorelli; Dhingra, Swati; Carless-Kane, Sandra; McGuinness, Claire; Paolucci, Alessandra; Jacobsen, Michele; Lorenzetti, Diane L.; Lorenzetti, Liza; Oddone Paolucci, Elizabeth
ABSTRACT: The ongoing COVID-19 pandemic has altered caring professions education and the range of technological competencies needed to thrive in today's digital economy. We aimed to identify the various technologies and design strategies being used to help students develop and translate professional caring competencies into remote working environments. Eight databases were systematically searched in February 2021 for relevant studies. Studies reporting on online learning strategies designed to prepare students to operate in emerging digital economies were included. Quality assessment was undertaken using the Effective Public Health Practice Project Quality Assessment Tool and/or the Joanna Briggs Institute Critical Appraisal Checklist for Qualitative Research. Thirty-eight studies were included and synthesized to report on course details, including technologies being used and design strategies, and study outcomes including curriculum, barriers and facilitators to technology integration, impact on students, and impact on professional practice. Demonstrations of remote care, videoconferencing, online modules, and remote consultation with patients were the most common instructional methods. Audio/video conferencing and online learning systems were the most prevalent technologies used to support student learning. Students reported increased comfort and confidence when working with technology and planning and providing remote care to patients. While a recent influx in research related to online learning and caring technologies was noted, study quality remains variable. More emphasis on assessment, training, and research is required to support students in using digital technologies and developing interpersonal and technological skills required to work in remote settings.